Exploring Perceptions of Barriers, Facilitators, and Motivators to Physical Activity Among Female Bariatric Patients: Implications for Physical Activity Programming. Issue 7 (September 2016) - Dikareva, A.; Harvey, W. J.; Cicchillitti, M. A.; Bartlett, S. J.; Andersen, R. E.
Purpose: To explore barriers, facilitators, and motivators to adopting and maintaining regular physical activity among women with obesity who have undergone bariatric surgery. Approach: Individual interviews with women 3 to 24 months post–bariatric surgery. Setting: Participants were recruited from a bariatric clinic in Montreal, Canada. Participants: Twelve women were recruited (mean age = 47 ± 9 years) using poster advertisements and word of mouth. Participants were on average 15 months postsurgery. Method: Each woman was interviewed once using a semistructured interview protocol. Recruitment was conducted until data saturation (i.e., no new information emerged). The interviews were transcribed, coded, and analyzed using inductive thematic analysis. Results: Three interrelated themes emerged: the physical body, appraisal of the physical and social self, and the exercise environment. Barriers included weight-restricted mobility, side effects of surgery, body dissatisfaction, compromised psychological health, competing responsibilities, a lack of exercise self-efficacy and social support, reduced access to accommodating facilities, lack of exercise knowledge, and northern climate. Participants reported postsurgical weight loss, weight and health maintenance, enjoyment, body image, and supportive active relationships, as well as access to accommodating facilities and exercise knowledge, as facilitators and motivators. Conclusion: Suggested physical activity programming strategies for health care professionals working with this unique population are discussed. Physical activity and health promotion initiatives can also benefit from a cultural paradigm shift away from weight-based representations of health.